Avaliação de um programa de capacitação de treinadores para a utilização de estabelecimento de metas no esporte - Sudo, Camila Harumi (2008)
The aim of this study was to assess the effects of a coach training program on the behaviors of a tennis coach while establishing goals for his athletes during practice. A 21-year – old coach with 3 years of experience, and 2 athletes, aged between 5 and 16 years old who have practiced and competed regularly took part in this research. The study was divided in three phase. During the baseline phase, 11 sessions of training were filmed and the percentage of occurrence of the instructions, encouragement, criticism/sarcasm,corrections and praise, given to athletes by their coach, were calculated. It was also recorded the type of drills used and the number of times in which the coach has registered the athletes development and his participation in the required drills. Following, it was initiated the intervention phase (Phase 2), consisting of four steps, totalizing 10 sessions. Each session was composed of the training of specific coach abilities (observe, register the athlete’s behavior, criterion and development time, provide feedback etc.) before practice and by the post-training follow-up with the athletes. Feedback was provided for the coach, during and after the training. Finally, during the post-intervention (Phase 3), procedures were set such as in baseline phase. The results showed that was an increase of the percentage of instructions, corrections and descriptive praise, and the decrease of the percentage of criticism/sarcasm, during and after intervention. It was also observed the increase of number of times when the development of the athletes were registered and the coach’s participation in the performed drills. It was seen that the knowledge obtained by the coach was used to interact with different students other than those. It was also observed the improvement on the athletes performance – who have achieved the established goals. Therefore, the results suggest the effectiveness of the intervention while training coaches in the use of the goal-setting strategy, as well as the need of further investigation using a larger number of coaches in sports other than tennis.